Temperature dependent bacteriophages of a tropical bacterial pathogen - Shan, Jinyu; Korbsrisate, Sunee; Withatanung, Patoo; Adler, Natalie Lazar; Clokie, Martha R. J.; Galyov, Edouard E. (Frontiers in Microbiology, 2014)
There is an increasing awareness of the multiple ways that bacteriophages (phages) influence bacterial evolution, population dynamics, physiology and pathogenicity. By studying a novel group of phages infecting a soil borne pathogen, we revealed a paradigm shifting observation that the phages switch their lifestyle according to temperature. We sampled soil from an endemic area of the serious tropical pathogen Burkholderia pseudomallei, and established that podoviruses infecting the pathogen are frequently present in soil, and many of them are naturally occurring variants of a common virus type. Experiments on one phage in the related model Burkholderia thailandensis demonstrated that temperature defines the outcome of phage-bacteria interactions. At higher temperatures (37°C), the phage predominantly goes through a lytic cycle, but at lower temperatures (25°C), the phage remains temperate. This is the first report of a naturally occurring phage that follows a lytic or temperate lifestyle according to temperature. These observations fundamentally alter the accepted views on the abundance, population biology and virulence of B. pseudomallei. Furthermore, when taken together with previous studies, our findings suggest that the phenomenon of temperature dependency in phages is widespread. Such phages are likely to have a profound effect on bacterial life, and on our ability to culture and correctly enumerate viable bacteria.